Adapting an intervention of brief problem-solving therapy to improve the health of women with antenatal depressive symptoms in primary healthcare in rural Ethiopia - Bitew, T.; Keynejad, R.; Myers-Franchi, Bronwyn; Honikman, S.; Sorsdahl, K.; Hanlon, C. (2022)
Background: Evidence-based brief psychological interventions are safe and effective for the treatment of antenatal depressive symptoms. However, the adaptation of such interventions for low- and middle-income countries has not been prioritised. This study aimed to select and adapt a brief psychological intervention for women with antenatal depressive symptoms attending primary healthcare (PHC) in rural Ethiopia. Methods: We employed the Medical Research Council (MRC) framework for the development and evaluation of complex interventions. Alongside this, we used the ADAPT-ITT model of process adaptation and the ecological validity model (EVM) to guide content adaptation. We conducted formative work, comprising a qualitative study, a series of three participatory theories of change workshops and an expert adaptation workshop to assess the needs of the target population and to select an intervention for adaptation. The adaptation process followed a series of steps: (1) training Ethiopian mental health experts in the original South African problem-solving therapy (PST version 0.0) and an initial adaptation workshop leading to PST Version 1.0. (2) Version 1.0 was presented to perinatal women and healthcare professionals in the form of a ‘theatre test’, leading to further adaptations (version 2.0). (3) Local and international stakeholders reviewed version 2.0, leading to version 3.0, which was used to train 12 PHC staff using clinical cases. (4) Finally, feedback about PST version 3.0 and its delivery was obtained from PHC staff. Results: In the first step, we modified case examples and terminology from the South African model, introduced an in-session pictorial flipchart for this low literacy setting, and added strategies to facilitate women’s engagement before translating into Amharic. In the second step, adaptations included renaming of the types of problems and inclusion of more exercises to demonstrate proposed coping strategies. In the third step, the components of motivational interviewing were dropped due to cultural incongruence. In the final step, refresher training was delivered as well as additional training on supporting control of women’s emotions to address PHC staff training needs, leading to the final version (version 4.0). Conclusion: Using a series of steps, we have adapted the content and delivery of brief PST to fit the cultural context of this setting. The next step will be to assess the feasibility and acceptability of the intervention and its delivery in antenatal care settings.